Microbiological hazard from the exhaust of a high-vacuum sterilizer. - Barbeito, M S (1976)
Data are presented which show the potential for release of viable microorganisms into the atmosphere from high-vacuum steam sterilizers during the evacuation cycle preceding application of steam under pressure. Bacillus subtilis var. niger spores, Serratia marcescens cells, and T1 coliphage disseminated into the sterilizer chamber as small particles from liquid suspensions, and dried spores of B. subtilis var. niger distributed on bulk discard materials were recovered from the atmosphere around pipes venting steam from the steam ejectors used to create chamber vacuum. Evaluation of the hazard involved is discussed, and the design, fabrication, and installation of a valved filter system for preventing release of viable microorganisms are presented. The filtration system utilized an F-700 water-resistant filter and was shown to eliminate the release of viable airborne microorganisms from a high-vacuum sterilizer. A method is presented for determining size requirements for an atmospheric vent filter in relation to the volume of a sterilizer.